Entinostat, a class I selective histone deacetylase inhibitor, plus exemestane for Chinese patients with hormone receptor-positive advanced breast cancer: A multicenter, randomized, double-blind, placebo-controlled, phase 3 trial - Binghe Xu; Qingyuan Zhang; Xichun Hu; Qing Li; Tao Sun; Wei Li; Quchang Ouyang; Jingfen Wang; Zhongsheng Tong; Min Yan; Huiping Li; Xiaohua Zeng; et al. (Elsevier, 2023)
Entinostat plus exemestane in hormone receptor-positive (HR+) advanced breast cancer (ABC) previously showed encouraging outcomes. This multicenter phase 3 trial evaluated the efficacy and safety of entinostat plus exemestane in Chinese patients with HR + ABC that relapsed/progressed after ≥1 endocrine therapy. Patients were randomized (2:1) to oral exemestane 25 mg/day plus entinostat (n = 235) or placebo (n = 119) 5 mg/week in 28-day cycles. The primary endpoint was the independent radiographic committee (IRC)-assessed progression-free survival (PFS). The median age was 52 (range, 28-75) years and 222 (62.7%) patients were postmenopausal. CDK4/6 inhibitors and fulvestrant were previously used in 23 (6.5%) and 92 (26.0%) patients, respectively. The baseline characteristics were comparable between the entinostat and placebo groups. The median PFS was 6.32 (95% CI, 5.30-9.11) and 3.72 (95% CI, 1.91-5.49) months in the entinostat and placebo groups (HR, 0.76; 95% CI, 0.58-0.98; P = 0.046), respectively. Grade ≥3 adverse events (AEs) occurred in 154 (65.5%) patients in the entinostat group versus 23 (19.3%) in the placebo group, and the most common grade ≥3 treatment-related AEs were neutropenia [103 (43.8%)], thrombocytopenia [20 (8.5%)], and leucopenia [15 (6.4%)]. Entinostat plus exemestane significantly improved PFS compared with exemestane, with generally manageable toxicities in HR + ABC (ClinicalTrials.gov #NCT03538171).